2019
DOI: 10.1063/1.5078379
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional structure of the unsteady wake of an axisymmetric body

Abstract: The near-wake of an axisymmetric body has been investigated using base pressure tappings and large scale Tomographic Particle Image Velocimetry (TPIV) at a Reynolds number of ReD = 3.2 × 105, based upon model diameter. Insights into the near-wake dynamics are provided by the application of Proper Orthogonal Decomposition (POD) to the pressure and the TPIV datasets. The first two POD modes show that the axisymmetric topology seen in the time averaged field is the result of the combination of different reflectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 45 publications
(82 reference statements)
4
25
0
Order By: Relevance
“…This is confirmed here, as an approximately 12 % drop is observed in the energy level of the first POD mode when wheels are added to the model (figure 9b). The weakening of the bi-stable lateral symmetry-breaking mode, following the loss of symmetry in the vertical direction, agrees also with the findings of Barros et al (2017), Bonnavion & Cadot (2018) and Pavia et al (2019b).…”
Section: Unsteady Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…This is confirmed here, as an approximately 12 % drop is observed in the energy level of the first POD mode when wheels are added to the model (figure 9b). The weakening of the bi-stable lateral symmetry-breaking mode, following the loss of symmetry in the vertical direction, agrees also with the findings of Barros et al (2017), Bonnavion & Cadot (2018) and Pavia et al (2019b).…”
Section: Unsteady Resultssupporting
confidence: 88%
“…Two of the wings were mounted vertically at the start of the contraction whilst the third wing was mounted ≈ 30 mm from the floor at the start of the working section, to seed the model underbody (figure 1d). With the seeding system in place, a limited increase in the free-stream turbulence intensity is expected, although this has been shown to be relatively limited by Pavia et al (2019b). The seeding arrangement allowed a stream-tube with a square cross-section of ≈ 400 mm × 400 mm (in the test section) to be seeded.…”
Section: Tomographic Pivmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, in the laminar regime, Del Taglia et al [13] found that the occurrence of this flow asymmetry is influenced by the jet blockage ratio and the Reynolds number, which can be integrated as a state parameter. Similar kinds of asymmetric flow patterns were also observed in other flow configurations, such as in turbulent wakes past blunt bodies [17][18] .…”
Section: Introductionsupporting
confidence: 77%